THE MOSQUE OF PROPHET YUNUS (PEACE BE UPON HIM) IN THE WAQF REGISTER OF THE MOSUL PROVINCE DURING THE LATE OTTOMAN PERIOD: “A HISTORICAL-DOCUMENTARY STUDY OF ITS RELIGIOUS, ADMINISTRATIVE, SCIENTIFIC, AND SERVICE FUNCTIONS” - Younis, Majid (Humanities Journal of University of Zakho, 2025)
The Mosque of Prophet Yunus (PBUH) is considered one of the most historically significant mosques in the Islamic world in general, and in Iraq in particular. It has received considerable attention from Muslims at large as well as from rulers, including caliphs, kings, and presidents across various historical periods. Beyond its religious significance, it is renowned as one of Iraq’s archaeological and historical landmarks, believed by the public to contain the tomb of Prophet Yunus (PBUH). This study explores the history of this mosque as a prominent center for religious, administrative, scientific, and public service activities. It particularly focuses on the key functions it performed during the final phase of the Ottoman era—specifically in the 19th century and the first quarter of the 20th century—based on information recorded in the Ottoman Endowment Register of Mosul.